2004
DOI: 10.1124/mol.104.007278
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Peroxisome Proliferator-Activated Receptor α-Regulated Genes in Dwarf Mice

Abstract: Defects in growth hormone secretion or signaling in mice are associated with decreased body weights (dwarfism), increased longevity, increased resistance to stress, and decreases in factors that contribute to cardiovascular disease and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Recent studies in Snell, GHRKO, and PAPPA‐KO mice have shown a common physiology that may control aging rate and multiple age‐related diseases (Murakami et al ., 2003; Boylston et al ., 2006; Brown‐Borg, 2006). These mice all exhibit high insulin sensitivity and an increased oxygen consumption with high levels of peroxisome proliferator‐associated receptor γ coactivator 1 (Pgc1α) from oxidative phosphorylation (Corton & Brown‐Borg, 2005; Stauber et al ., 2005). Similarly, CNOT3 heterozygous mice (Morita et al ., 2011) have been shown to have increased insulin sensitivity, oxidative phosphorylation (including higher Pgc1α expression), and oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in Snell, GHRKO, and PAPPA‐KO mice have shown a common physiology that may control aging rate and multiple age‐related diseases (Murakami et al ., 2003; Boylston et al ., 2006; Brown‐Borg, 2006). These mice all exhibit high insulin sensitivity and an increased oxygen consumption with high levels of peroxisome proliferator‐associated receptor γ coactivator 1 (Pgc1α) from oxidative phosphorylation (Corton & Brown‐Borg, 2005; Stauber et al ., 2005). Similarly, CNOT3 heterozygous mice (Morita et al ., 2011) have been shown to have increased insulin sensitivity, oxidative phosphorylation (including higher Pgc1α expression), and oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet clear how the Snell dwarf mutation, and the drugs tested, lead to extended lifespan, and it is possible that the effects on proteasome biology reflect different cellular or physiological mechanisms. Elevated immunoproteasome expression in Snell dwarf mice is unlikely to be caused by increases in IFN-γ responses because IFN-γ receptor levels are downregulated in Snell dwarf mice (56). Elevation of TNF-α levels, seen in Snell dwarf mice (57), is a potent inducer of immunoproteasome expression (58).…”
Section: Discussionmentioning
confidence: 99%
“…Several peroxisome proliferator-activated receptor α-regulated genes and gene products including those involved in β-oxidation of fatty acids are elevated in dwarf mice (including Ames, Snell, and GHRKO mice; Stauber et al 2005).…”
Section: Discussionmentioning
confidence: 99%